2013
DOI: 10.1246/cl.130294
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Trifluorovinyl Compounds by Lithium Salt-promoted Monoalkylation of Tetrafluoroethene

Abstract: Treatment of tetrafluoroethene (TFE) with diethylzinc in the presence of lithium iodide gave 1,1,2-trifluoro-1-butene in moderate yield. In the absence of lithium iodide, however, the nucleophilic addition of diethylzinc to TFE proceeded very slowly to afford ethyl 1,1,2,2-tetrafluorobutylzinc. The addition of lithium iodide to a solution of ethyl-1,1,2,2-tetrafluorobutylzinc resulted in a smooth transformation into 1,1,2-trifluoro-1-butene. In the presence of lithium chloride, the reaction of TFE with benzyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Additionally, selective monosubstitutions of TFE with diethylzinc or organomagnesium compounds in the presence of a lithium salt have been reported. 8 TFE is one of the most important materials for the production of fluorine-containing polymers such as PTFE and is an economical and environmentally benign feed stock with near-zero global warming potential (GWP) for the fluorine industry.…”
mentioning
confidence: 99%
“…Additionally, selective monosubstitutions of TFE with diethylzinc or organomagnesium compounds in the presence of a lithium salt have been reported. 8 TFE is one of the most important materials for the production of fluorine-containing polymers such as PTFE and is an economical and environmentally benign feed stock with near-zero global warming potential (GWP) for the fluorine industry.…”
mentioning
confidence: 99%
“…2.4 Lithium Salt Promoted the Selective Monoalkylation of TFE We have also developed related monoalkylation reactions of TFE, which involve a classic addition elimination mechanism without the use of a palladium catalyst (Scheme 12). 25 In the presence of lithium iodide, the reaction of TFE with diethylzinc (15) in t BuCN at 60 for 24 h resulted in the formation of 1,1,2 tri uoro 1 butene (16) in 51% yield. The yield of 16 at approximately 50% was rationalized by the lack of reactivity of ethylzinc iodide toward TFE under the same reac- tion conditions.…”
Section: Hiyama Type Cross Coupling With Arylsilanesmentioning
confidence: 99%
“…11 Furthermore, we also demonstrated that the addition of lithium chloride improved the rate and selectivity of the reaction of benzylmagnesium chloride (20a) with TFE at room temperature for 0.5 h to give 21a in a quantitative yield (Scheme 13). 25 Lithium chloride might enhance the reactivity of 20a as a result of the formation of the ate species. 14 Although simple alkylmagnesium reagents such as ethylmagnesium chloride retarded the reaction, both benzyl and allyl magnesium chloride derivatives participated in the reaction.…”
Section: Hiyama Type Cross Coupling With Arylsilanesmentioning
confidence: 99%
“…For instance, most of the initial preparation routes for trifluorostyrenes required multistep reactions [13][14][15][16]. A few reactions substituting the fluorine atom on fluoroolefines, including tetrafluoroethylene (1; TFE), with a carbon nucleophile are considered classic procedures [17][18][19][20][21][22][23]. These reactions involve an addition-elimination mechanism, and they often suffer from undesired side-reactions, such as a multi-substitution reaction, even at low reaction temperatures [17,19].…”
Section: Introductionmentioning
confidence: 99%